Analisis Pengaruh Penggunaan Uang Elektronik Terhadap Gaya Hidup Generasi-Z di Kota Denpasar - Gde Bagus Pradipta Nandana Putu; Putu Sri Arta Jaya Kusuma (AKUNTANSI 45, 2024)
Generation Z, known for their familiarity with technology, is increasingly using electronic money (e-money) in transactions. This research aims to analyze the influence of e-money use on the lifestyle of generation Z in Denpasar City. Data was collected through a survey of 57 generation Z respondents in Denpasar City. The research results show that the use of e-money has a significant influence on lifestyle, level of participation in social and economic activities, and perceptions about generation Z's financial management so that they do not behave consumptively. This research provides implications for stakeholders in formulating appropriate policies and programs for generation Z, as well as for generation Z themselves in managing their finances and lifestyle more wisely.